Chemical and multi-scale material properties of recycled and blended asphalt binders. (20th November 2020) - Lakshmi Roja, K.; Masad, Eyad; Vajipeyajula, Bhaskar; Yiming, Wubulikasimu; Khalid, Eisha; Shunmugasamy, Vasanth C.
Abstract: Motivated with sustainability and economic factors, there is a rapid increase in the use of recycled asphalt pavement (RAP) material in the construction of new asphalt pavements. This necessitates the development of better understanding of the interaction between recycled and virgin binders, as well as studying the influence of this interaction on the properties of the blended binder. This paper provides in-depth evaluation of these properties at various scales using chemical, mechanical and rheological tests. This study involved the use of binders with different proportions of RAP (0, 15, 25, 35 and 100%). The chemical characterization of these binders was carried out using Fourier Transform Infrared Spectroscopy (FTIR), and the results showed that higher peak levels of CO and SO bonds were observed with the increase in RAP binder content. Atomic Force Microscopy (AFM) imaging of these binders showed that the surface roughness increased with an increase in RAP content especially when the RAP proportion exceeded 25%. The multiple stress creep recovery (MSCR) test was used to measure the rutting resistance, and the linear amplitude sweep test (LAS) was used to evaluate the fatigue resistance. There was slight improvement in rutting resistance with an increase in RAP content; however, the fatigue resistance degraded with the addition of RAP. The moduli/stiffness of virgin, RAP and blended binders was determined using Dynamic Shear Rheometer (DSR), Nanoindentation (NI), and AFM. The moduli obtained from these three techniques increased exponentially and at similar rates up to 25% of RAP. However, the dynamic modulus from DSR increased at a higher rate than the nano-scale moduli at higher RAP contents. This finding suggests that the nano-scale interactions were not influenced by the increase in RAP content as the DSR measurements of dynamic modulus and fatigue life values imply. The nano-scale understanding of blended binder offers opportunities for better engineering and accommodation of RAP in asphalt mixtures.